Integration of STEAM and ESD: Improving the understanding of fluid concepts and creativity - Khoiri, Nur; Roshayanti, Fenny; Widarti, Rezki (Journal of Education and e-Learning Research, 2023)
The aim of this study was to develop a learning model that integrated ESD-oriented STEAM with fluid ideas to produce ESD-oriented STEAM-based learning. This study employs the Borg and Gall model which is simplified into three steps. The effectiveness and documentation were evaluated using questionnaires for experts and educational practitioners, observation sheets for student creativity and pre- and post-test sheets. The data analysis involves both quantitative and qualitative methods. The findings demonstrated the characteristics of STEAM-based physics learning tools including increased creativity and student learning outcomes. Analyzing how ESD-focused STEAM-based learning resources are used in the developed fluid material yields beneficial results. Student learning outcomes increased in the moderate category. The average score for student creativity was 86.12% in the very good category showing that the usage of learning resources including worksheets based on STEAM subjects and ESD was successful in enhancing creativity and student learning outcomes. This study has implications for improving student interest in physics education. The findings of this study can also be used to advise curriculum designers to incorporate this model for physics teachers to use while instructing physics in their courses.